Using vocal consequences with TAGteach™ to teach novel dance movements to adults. (22nd April 2022) - Arnall, Robin; Griffith, Annette K.; Kalafut, Kathryn; Spear, Jack
Abstract: Researchers have demonstrated the effectiveness of TAGteach™ to develop skills across a variety of sports, such as football, golf, and dance, however, the role of vocal consequences in skill development is not yet fully understood. To date, there have been no studies that have examined the effects of these two interventions. Therefore, the purpose of this study is to demonstrate the effects of vocal consequences and TAGteach on the skill acquisition of a series of dance movements for two adults aged 28 and 43. Neither participant made substantial gains in skill acquisition during the vocal consequences (e.g., "great, " "not quite") phase, yet each demonstrated increased skill acquisition for all movements during the TAGteach phase. Although no direct comparison occurred, the data suggest that the TAGteach intervention was more effective for increasing skill acquisition of the movements across a multiple baseline of movements. At the 2‐week and 4‐week follow‐ups, both participants maintained higher percentages of correct tag point demonstration than were displayed during baseline or the vocal consequence phase.